Joaquim B. de Carvalho. 2013. Why there is no backness: the case for dismissing both [coronal] and [dorsal]. In J.-L. Léonard & S. Naïm (ed.) Backness and backing. Munich: Lincom, pp. 45-58. - Silva, Carlos (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2019)
.